(untitled) (Quest Journal of Management and Social Sciences, 2022)
Background: Common stock return is a major concern for investors and the management of the firm. Investors always want to increase their values of common stock; thus, they always want to increase common stock returns. The investor for investment prefers the company that provides better common stock return. Thus, the management of the firm always wants to increase common stock returns. The common stock return is affected by so many internal and external factors. Internal factors are the firm-specific factors that the firm’s management can control, and external factors are the macroeconomic factors that the individual firm cannot control. Generally, firm-specific factors include the size of the firm, book-to-market equity, earnings yield, cash flow yield, dividend yield, leverage, return on assets, sales-to-price ratio etc. If the firm’s management identifies these factors influence, they can increase their common stock return. Objective: This paper aims to investigate the effect of firm-specific variables on the stock return of Nepalese commercial banks. Methods: To observe the influence of firm-specific variables on stock return of Nepalese commercial banks, multivariate regression analysis have been applied. In regression analysis stock return is taken as dependent variable and firm-specific variables such as size (lnME), book-to-market equity (BE/ME), earnings yield (E/P), dividend yield (D/P), return on assets (ROA), earning per share (EPS), sales per share to stock price (S/P) ratio have been taken as explanatory variables. Findings: This paper finds the positive impact of D/P and EPS, and the negative effect of E/P, ROA and S/P ratio on the stock return of Nepalese commercial banks. Conclusions: This paper concludes that Nepalese commercial banks can increase common stock return by increasing D/P and EPS and lowering E/P, ROA and S/P ratios. Implication: The findings of this study can be implemented by investors for investment decisions and bank management to maximize the stock returns of Nepalese commercial banks.